Curing parameters' influences of early-age temperature field in concrete continuous rigid frame bridge. (1st September 2021) - Zeng, Yong; Zeng, Yutong; Jiang, Dong; Liu, Shanhong; Tan, Hongmei; Zhou, Janting
Abstract: The unstable change of early temperature field during concrete curing of box girder could lead to the thermal deformation and autogenous shrinkage deformation of concrete, make the concrete crack early, and even affect the subsequent mechanical performance. In order to study the variation law of the early-age temperature field of the box girder concrete and to seek the method to control the variation of the temperature field of the box girder concrete, the No.0 box segment with the most complex structure and the largest volume in the bridge was selected as the research object. The early-age temperature field of No.0 box segment after pouring was simulated by Midas/FEA and the correctness of the simulation was verified by field measurement. Then the time-history law of early-age temperature field of the box girder under the coupling effect of hydration heat and ambient temperature was studied, and the time-history law of the early-age temperature field of the box girder was investigated by changing different concrete curing parameters. The results show that the larger the local size is, the larger the temperature difference is. The selection of formwork's material and thickness should integrate the factors of formwork bearing capacity and thermal insulation performance. The reasonable selection of formwork can effectively control the core temperature and the temperature difference between the inside and outside of the box girder. Formwork installation temperature and wind velocity have a great influence on the temperature difference between the inside and outside of the box girder. The research results can provide technical support for controlling the early-age temperature field changes of box girder concrete, be used to provide a theoretical basis for the best selection of formwork and the selection of the best concrete curing conditions, and help to improve efficiencies in the uses of human capital, energy, and building materials in engineering construction.